Os Tempos do Império: Uma Análise da Reforma do Ensino Livre de 1879 - Sousa, Francisco Alencar de (2006)
Abstract The purpose of this work is to analyze the Brazilian Reforma do Ensino Livre (Free Teaching Law Reform) established by the Bill number 7247 of April 19th, 1879. In order to do that, the study was focused on a time limitation involving the last decades of the Empire period until the Republic Proclamation, that is, from 1870 to 1889. This time limit was necessary to include the educational debate that came before and after the implementation of the Bill. We tried to understand the Reforma do Ensino Livre as a revealing interpretation of the Brazilian society´s transformation process and also the historic period in constant change, looking for the relations between the teaching reform and the set of the reforms in various fields, such as, political, economical and cultural ones. The methodology used in this work comprised the selection of central themes in the Bill that established the Reforma do Ensino Livre , in 1879, which is the main object to be analyzed here. The main document body in this research is composed by two main sources: the first one is the Bill of 1879 and the second one comprises the Empire´s ministry reports that were presented to the General Legislative Assembly and also the reports of the president of Rio de Janeiro province. The results of the research comprehended that the political game and the social purposes were mediated by the negotiations or reforms, once the projects were the modernization of the institutions, without provoking great changes in the politics paths of those who define the steps in the process of the making of the nation. Each institution, created or reorganized, should make a person capable of following rules, and the maximum of freedom would be the competition among their peers. In this way, it was expected that the school was be the place where the first moral lessons should be taken. In order to do that the State administrators kept the control of the morality that the elite defended as the principle of the students´ background education.